Mawara An-Nahr Judiciary System And Its Characteristics - Bekmirzaev Ilkhomjon Israiljonovich; Ergashov Hasanboy Faizullo o’g’li (Penerbit Jurnal Indonesia, 2024)
This article analyzes the development of the judicial system in the Mawara an-Nahr region and its key aspects related to the existing qadi system. It demonstrates how government structures and judicial practices evolved under the influence of the Hanafi school of thought, as well as the strengthening of the qadi system during the Abbasid period and its impact on the judicial system in Mawara an-Nahr. The article provides a detailed description of the reforms carried out during the Abbasid period, the formation of the judicial system, and the establishment of new judicial positions and practices related to civil courts.